Challenging Binaries by Saying Good Bi: Perceptions of Bisexual Men's Identity Legitimacy. Issue 3 (2nd July 2016) - Morrison, Katheryn E.; Gruenhage, Jordan M.; Pedersen, Cory L.
ABSTRACT: Since the 1970s, sexuality research has focused on a multitude of factors precipitating and influencing sexuality discrimination. However, the unique social positioning of bisexual individuals is notably absent in comparison to discussions of discrimination experienced by lesbians and gay men. This research examined bisexual discrimination at an institution in Western Canada, and among larger online communities predominantly accessed in North America. An online questionnaire measured 306 participants' negative attitudes toward bisexual men and bisexuality. Results indicated that levels of bisexual discrimination for most participants were influenced by altering the content of an article that participants read before completing a measure of bisexual discrimination. Biphobia scores remained relatively stable among bisexual participants regardless of gender, whereas scores were revealed to be more variable among straight participants. By illustrating the contrasting ways in which individuals perceive information about bisexual people, the findings of this study suggest a new understanding of bisexual discrimination that differs from the existing literature.